SIKAP SISWA TERHADAP SAINS PADA PEMBELAJARAN IPA DI SMP NEGERI 2 PASIR PENYU KELAS VIII - Heri Nurkholis; Fakhruddin Z Fakhruddin Z; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aimed to determine student attitude of science on learning grade VIII SMP Negeri 2 Negeri Pasir Penyu. The kinds of this study was a survey. The population in this study was student of SMP Negeri 2 Pasir Penyu and sample in this study was students grade VIII consisted of four classes used purposive sampling. The data was collected by nontest with questionnaire . The data was analyzed by using descriptive statistic techniques. The result of this study shows that indicator of student attitude was high, except for perspective of sains was lowKeywords : Student Attitude Of Science, Science Learning